The Stability and Hopf Bifurcation of the Prey-predator System with Delay and Migration (Journal of Partial Differential Equations, 1994)
In this paper we first investigate the system with the inftuence of delay and migration and give a theoretical analysis of the alternative change of the stability discovered by Stepan with computer program, then we reduce the system with the center manifold theorem and present an approximation form of Hopf bifurcation solutions. Finally we give the numerical analysis of stability for a concrete periodic solution.
Keywords: Delay; migration; alternative change of stability; center manifold; Hopf bifurcation